Design and implementation of online battery monitoring and management system based on the internet of things - Chen, Kena; Luo, Lei; Lei, Wei; Lv, Pinlei; Zhang, Liang (Frontiers in Energy Research, 2024)
Battery pack provides the backup power supply for DC systems of power substations. In the event of an AC power outage or other accidents, it is an important guarantee for the reliable operation of power substation. To prevent possible failures, batteries usually require careful maintenance. Common methods are online monitoring, condition assessments, and health management. Among these, model-based techniques are widely used for battery monitoring and prognostics optimization. Data-driven methods are a good alternative solution when no mathematical models are available. As substations develop towards intelligent and unmanned modes, this paper proposes an online battery monitoring and management system based on the "cloud-network-edge-end" Internet of Things (IoT) architecture. The system has functions including ledger management, basic battery information display, real-time display of battery monitoring data, and the visualization of battery alarm information. It can implement online monitoring and intelligent maintenance management for battery operating status. The designed and developed system has been applied in the monitoring and management of the battery for a 110kV offshore substation, mainly providing battery maintenance suggestions and fault alarm prompts. This verifies the effectiveness and convenience of IoT-based systems for the monitoring and management of batteries.